(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the incidence rates of three common healthcare-associated infections: ventilator-associated pneumonia (VAP), central line-associated bloodstream infection (CLABSI), and catheter-associated urinary tract infection (CAUTI) at the Intensive Care Unit of Bach Mai Hospital from 2024-2025. Methods: A descriptive observational study of 1,654 patients treated for ≥2 days at the Intensive Care Unit of Bach Mai Hospital from August 1, 2024, to July 31, 2025. Results: The overall incidence rate of the three healthcare-associated infections was 18.3%, with an incidence density of 14.1 cases/1000 patient-days. The incidence rate of VAP was 15.2% with a density of 12.7 cases/1000 ventilator-days; CLABSI incidence rate was 3.9% with a density of 3.8 cases/1000 central line-days; CAUTI incidence rate was 14.7% with a density of 15.8 cases/1000 catheter-days. Conclusion: The overall incidence rate of the three healthcare-associated infections was 18.3%, with an incidence density of 14.1 cases/1000 patient-days. Ventilator-associated pneumonia was the most common infection, with an incidence rate of 15.2% and an incidence density of 12.7 cases/1000 ventilator-days